RETHINKING ISLAMIC THEOLOGY Mengagas Teologi Sosial dalam Konteks Pluralisme dan Multikulturalisme (Perspektif Pemikiran Teologi Fethullah Gulen) - Muhammad Said (Institut Agama Islam Negeri (IAIN) Manado, 2018)
Abstract This article elaborate about the neccesity of renewal Islamic theology in the context of pluralism and multiculturalism. One of contemporary Muslim schoolars, Fethullah Gulen, could be considered among the most influential Muslim theologians of our time. His work focus on redefining the nature of Islamic discourse in the contemporary world by doing interreligious and intercultural dialogue. Today, we need to shift our paradigm from classical kalam which dogmatic, abstract, and exclusive to more practical theology based on life and contemporary needs, which is called “social theology”. Gulen’s theological discourse distinguished for his support of democracy, humanisme, openness to globalization, progressiveness in integrating tradition with modernity, and to make sense of pluralistic-piety. Keyword: Kalam, Social-Theology, Pluralitic-Piety, MulticulturalismeAbstrak. Artikel ini menguraikan tentang necseity pembaharuan teologi Islam dalam konteks pluralisme dan multikulturalisme. Salah satu murid sekolah Muslim kontemporer, Fethullah Gulen, dapat dianggap sebagai salah satu teolog Muslim paling berpengaruh di zaman kita. Karyanya fokus pada mendefinisikan kembali sifat wacana Islam di dunia kontemporer dengan melakukan dialog antaragama dan antarbudaya. Saat ini, kita perlu menggeser paradigma kita dari kalam klasik yang dogmatis, abstrak, dan eksklusif ke teologi yang lebih praktis berdasarkan pada kehidupan dan kebutuhan kontemporer, yang disebut